2009
DOI: 10.1177/230949900901700201
|View full text |Cite
|
Sign up to set email alerts
|

Two-Plate Fixation for Humeral Shaft Nonunions

Abstract: Purpose.To review 22 patients who underwent 2-plate fixation for non-union of the humeral shaft. Methods. 13 women and 9 men aged 32 to 76 (mean, 48) years underwent fixation for non-union of the humeral shaft, using a 2-plate construct, together with decortication, debridement, and bone grafting. The two 3.5-mm reconstruction plates were parallel and lying at 90º to each other and fixed with screws purchasing into at least 6 cortices of each fragment for both plates. Fractures were located in the upper third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
6
22
0
1
Order By: Relevance
“…Despite the good results observed with different surgical techniques, advanced age seems to be a clear risk factor for failure. 2,6,11,12 Volgas et al 3 assessed the impact of several risk factors on the outcome and nonunion rate of humeral fractures. Advanced age, comorbidities, and previous surgeries all contributed to malignant nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the good results observed with different surgical techniques, advanced age seems to be a clear risk factor for failure. 2,6,11,12 Volgas et al 3 assessed the impact of several risk factors on the outcome and nonunion rate of humeral fractures. Advanced age, comorbidities, and previous surgeries all contributed to malignant nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports satisfactory results with all of these devices. 2,5,6,[10][11][12][13][14][15] In patients with osteoporotic bone, clinical and biomechanical studies have observed significantly improved stability with the use of a locking plate. 2,16 In light of these findings, the current 2 patients were treated with a Synthes LCP plate, which allows use of either a locking or a compression screw in any hole.…”
Section: Discussionmentioning
confidence: 99%
“…Plate osteosynthesis remains the gold standard of surgical treatment. Plate fixation results in high union rates but requires extensive dissection and soft tissue stripping [3]- [5]. The most commonly used approaches for treating these fractures are posterior and anterolateral [6]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kırık hattında stabiliteden şüphelenilen olgularda, anteriordan ikinci bir plak uygulanabilir. [7] Ardından, kırık sahasının ya kortikospongiyöz cips greftlerle (Şekil 9) ya da iliak kanattan alınan takoz greft (Şekil 10) ile desteklenmesi Şekil 8. Kırık parçaları arasına kompresyonu sağlamak için lag vidası uygulanmış olgu.…”
Section: Humerus Kaynamamalarıunclassified